2019
DOI: 10.7717/peerj.6462
|View full text |Cite
|
Sign up to set email alerts
|

Grazing exclosures solely are not the best methods for sustaining alpine grasslands

Abstract: Background Grazing is widely regarded as a critical factor affecting the vegetation structure, productivity and nutritional value of natural grasslands. To protect and restore degraded grasslands, non-grazed exclosures are considered as a valuable tool. However, it is not clear whether long term non-grazed exclosures of grazers can improve the condition and nutritional value of vegetation and soil properties. Methods We have compared the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Grazing exclosure is beneficial for soil C sequestration in degraded alpine grassland (Yu, Chen, Sun, & Huang, 2019), it also increased the aboveground biomass and coverage of plant, soil properties. However, long‐term grazing exclosure decreased biodiversity (Yao, Wu, Gong, Lang, & Wang, 2019), rotational grazing therefore would be a better grassland management strategy. Researches confirmed that rotational grazing improved ground cover and animal production (McDonald, Lawrence, Kendal, & Rader, 2019), biomass (Boavista, Trindade, Overbeck, & Müller, 2019), functional diversity (Li et al, 2019), and alleviate soil erosion (Sanjari, Yu, Ghadiri, Ciesiolka, & Rose, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Grazing exclosure is beneficial for soil C sequestration in degraded alpine grassland (Yu, Chen, Sun, & Huang, 2019), it also increased the aboveground biomass and coverage of plant, soil properties. However, long‐term grazing exclosure decreased biodiversity (Yao, Wu, Gong, Lang, & Wang, 2019), rotational grazing therefore would be a better grassland management strategy. Researches confirmed that rotational grazing improved ground cover and animal production (McDonald, Lawrence, Kendal, & Rader, 2019), biomass (Boavista, Trindade, Overbeck, & Müller, 2019), functional diversity (Li et al, 2019), and alleviate soil erosion (Sanjari, Yu, Ghadiri, Ciesiolka, & Rose, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, grazing exclusion has been widely used in Inner Mongolia for curbing grassland degradation and restoring damaged ecosystems (Bai et al, 2004;Hao et al, 2014). However, the effects of grazing exclusion are controversial depends on its vegetation types, environmental conditions, and duration (Jing et al, 2014;Yan & Lu, 2015;Yao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change appears to be a significant driver on arid grasslands [20,50,51,137] while it is not mentioned in humidity grasslands analysis. On the other hand, light grazing intensity or grazing exclusion, have different effects depending on the bioclimatic region, with a positive effect on arid environments [57,58], and a negative one on humidity regions [59,60]. Regarding consequences, desertification is exclusively reported on arid and semiarid areas [9].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, extreme under-grazing (or grazing abandonment) could also be a source of degradation affecting productivity and species composition. Although long term livestock exclosures increased standing biomass and vegetation cover, and they may be a useful management tool to restore the vegetation in degraded grassland of arid regions [57,58], they sometimes decreased grassland biodiversity [59,60] and ANPP [59].…”
Section: Which Are the Main Drivers That Influence Grassland Degradatmentioning
confidence: 99%